Factors associated with psychoactive substance use among youth in urban and rural local government areas of Kano State, Nigeria: a comparative cross-sectional study - Iliyasu, Usman; Musa, Zakka; Adeyemo, Queen E.; I. Shehu, Aliyu; Mohammed, Nazeef; R. Hussain, Abba; I. Kurba, Ibrahim; Isma’il, Musa; A. Ibrahim, Bello; M. Suleman, Ibrahim; E. Charles, Esekhaigbe; A. Joshua, Istifanus (International Journal of Research in Medical Sciences, 2026)
Background: Substance use among youth remains a major public health challenge in Nigeria, with limited community-based data from northern regions. This study assessed the prevalence, types, and factors associated with psychoactive substance use among youth in urban and rural local government areas (LGAs) of Kano State, Nigeria. Methods: A comparative cross-sectional study was conducted from December 2021 to March 2022 among 392 youth aged 15-24 years recruited from congregate settings in one urban and one rural LGA. Multistage sampling was used. Interviewer-administered questionnaires assessed socio-demographics and substance use. Data were analysed using SPSS version 20. Multivariable logistic regression identified factors associated with substance use, with significance set at p<0.05. Results: The prevalence of psychoactive substance use was 77.8% overall (urban: 88.7%; rural: 67.0%). Commonly used substances included tobacco products (urban: 87.2%; rural: 65.5%), cannabis (urban: 86.2%; rural: 60.9%), tramadol (urban: 83.6%; rural: 66.5%), and alcohol (urban: 59.5%; rural: 56.3%). In urban LGA, independent factors associated with substance use were lower income (<₦ 50,000: aOR=20.41, 95% CI: 6.33-66.60, p=0.001), and earlier age at initiation (≤16 years: aOR=2.72, 95% CI: 1.34-5.52, p=0.005; 17-20 years: aOR=2.72, 95% CI: 2.00-3.71, p=0.001). In rural LGA, associated factors included no formal education (aOR=2.31, 95% CI: 1.11-4.83, p=0.026), student status (aOR=4.13, 95% CI: 1.68-10.19, p=0.002), and lower income (aOR=2.11, 95% CI: 1.43-3.11, p=0.001). Conclusions: Prevalence of psychoactive substance use is high, particularly in urban areas. Strengthening substance use prevention programs, improving educational access, economic empowerment, and youth engagement initiatives may reduce substance use among at-risk youth.